EXPERIMENTAL QUASI-STEADY DENSITY CURRENTS - Alexander J.; Mulder T. (My University, 2002)
Hyperpycnal flows may be important mechanisms for transporting particles from continents to oceans given their frequency of generation at many modern river mouths. Their deposits are probably very common in the rock record, although they are not frequently recorded in the literature. These currents may last longer and be steadier than surge-like turbidity flows and consequently their deposits are likely to be significantly different. In this paper simple laboratory experiments are used to investigate how flows and deposits may vary. The thickness of the experimental flows near the flow front varies with distance from the source depending on slope, effluent discharge, grain size and sorting. Runout distance varies with the proportion of fine-grained sediment rather than with mean grain size. Flow front velocity varies with effluent discharge and sediment concentration and in a complex manner with mean grain size and sorting. The variation of deposit mass with runout distance depends on proximal slope angle and the maximum mass per unit area (approximating to bed thickness) is inversely dependent on slope angle. Variation in initial suspended particle concentration results in deposits of similar shape but different volume. Although the total mass of the deposit depends on the discharge the maximum mass per unit area (approximating to maximum bed thickness) does not. The distance over which particles are deposited increases and the deposit flattens as particles are deposited progressively further downstream at higher discharges, perhaps relating to more efficient turbulent suspension at higher Re (more complete energy cascade), in addition to longer horizontal component of settling trajectory at higher velocity. The amplitude of mass variation depends on the grain size. As with laboratory surges [Gladstone et al., Sedimentology (1998) 833–844], the finer the sediment the more efficient is the sediment transport.